Electronically Tunable Voltage-Mode Multiphase Sinusoidal Oscillator with Low Output Impedance Nodes Employing VD-DIBAs - Duangmalai, Danupat; Manasri, Thosapol; Kwawsibsam, Adisorn; Jaikla, Winai (My University, 2023)
The multiphase sinusoidal oscillator (MSO) is useful for various electrical and electronic applications. This study aims to design an MSO employing voltage differencing differential input buffered amplifiers (VD-DIBAs). The design procedure is based on cascading the first-order low-pass filter. Each phase consists of a VD-DIBA, two resistors, and a grounded capacitor. An odd-phase system without requiring an additional amplifier. The frequency is electronically controlled through the bias current without affecting the condition. The sinewave amplitudes and the phase difference between each waveform are identical. The proposed MSO is designed to obtain three-phase waveforms (n = 3). PSPICE simulation demonstrates the performance of the proposed oscillator with 0.18 μm TSMC CMOS parameters with ±0.9 V power supply. The feasibility of the proposed MSO is also verified with experiments using the VD-DIBA constructed from commercial integrated circuits (ICs) with a ±5 V power supply. The simulated and experimental results align with theoretical predictions
Keywords: multiphase sinusoidal oscillator; odd-phase system; VD-DIBA; voltage mode